The Antidepressant Sertraline Reduces Synaptic Transmission Efficacy and Synaptogenesis Between Identified Lymnaea Neurons - Chow, Jennifer; Thompson, Andrew J.; Iqbal, Fahad; Zaidi, Wali; Syed, Naweed I. (Frontiers in Marine Science, 2020)
The incidence of depression among humans is growing worldwide, and so is the use of selective serotonin reuptake inhibitors (SSRIs), such as sertraline hydrochloride. Our fundamental understanding regarding the mechanisms by which these antidepressants function and their off-target synaptic effects remain poorly defined, owing to the complexity of the mammalian brain. As all brain functions rely on proper synaptic connections between neurons, we examined the effect of sertraline on synaptic transmission, short-term potentiation underlying synaptic plasticity and synapse formation using identified neurons from the mollusk Lymnaea stagnalis. Through direct electrophysiological recordings, made from soma-soma paired neurons, we demonstrate that whereas sertraline does not affect short-term potentiation, it reduces the efficacy of synaptic transmission at both established and newly formed cholinergic synapses between identified neurons. Furthermore, Lymnaea neurons cultured in the presence of sertraline exhibited a decreased incidence of synaptogenesis. Our study provides the first direct functional evidence that sertraline exerts non-specific effects - outside of its SSRI role - when examined at the resolution of single pre- and post-synaptic neurons.